The Evaluation of Cooled Particles’ Parameters by Instruments of Nonlinear Metrology - Machekhin, Yu. P.; Kurskoy, Yu. S. (ВКФ «Фавор ЛТД», 2015)
In the article the task of laser Doppler cooling of particles (atoms, ions and molecules), which has important applications for physics and metrology, is considered. It is shown that the laser cooling is the interaction process between a deterministic system of laser radiation and a chaotic system of moving particles. For monitoring and estimation of the cooling particles’ parameters it’s proposed to use the methods and instruments of Nonlinear Metrology that were designed for measurement of nonlinear dynamic systems parameters. The formula for estimating of the laser radiation Shannon entropy, as a function of a laser frequency, is obtained. The results allow to evaluate the change of the entropy of the cooling particles system after a given number of cycles “absorption — spontaneous emission of photons”, which opens the new possibility for control of laser cooling process and estimate of temperature with small discrete values.
Keywords: laser cooling; Shannon entropy